Linguistic Exploration and Language Diversity in Bintuni Bay, West Papua: Sociolinguistic Study and Local Language Preservation - Saefullah, Rifki; Irman, Dede (Communication In Research And Publications, 2025)
The linguistic diversity in Bintuni Bay, West Papua, reflects the cultural richness of its people. This study identified seven languages ​​spoken by various ethnic communities in the region. Muna is the most widely spoken language and has a